Selinexor and COVID-19: The Neglected Warden - Mostafa-Hedeab, Gomaa; Al-kuraishy, Hayder M.; Al-Gareeb, Ali I.; Welson, Nermeen N.; El-Saber Batiha, Gaber; Conte-Junior, Carlos Adam (Frontiers in Pharmacology, 2022)
A novel severe acute respiratory distress syndrome coronavirus type 2 (SARS-CoV-2) has been confirmed as the cause of the global pandemic coronavirus disease 2019 (COVID-19). Different repurposed drugs have been trialed and used in the management of COVID-19. One of these agents was the anti-cancer Selinexor (SXR). SXR is an anti-cancer drug that acts by inhibition of nuclear exportin-1 (XPO1), which inhibits transport of nuclear proteins from the nucleus to the cytoplasm, leading to the induction of cell-cycle arrest and apoptosis. XPO1 inhibitors had antiviral effects, mainly against respiratory syncytial virus (RSV) and influenza virus. SXR inhibits transport of SARS-CoV-2 nuclear proteins to the cytoplasm with further inhibition of SARS-CoV-2 proliferation. SXR has the ability to prevent the development of a cytokine storm in COVID-19 by inhibiting the release of pro-inflammatory cytokines with the augmentation release of anti-inflammatory cytokines. In conclusion, SARS-CoV-2 infection is linked with activation of XPO1, leading to the triggering of inflammatory reactions and oxidative stress. Inhibition of XPO1 by Selinexor (SXR), a selective inhibitor of nuclear export (SINE), can reduce the proliferation of SARS-CoV-2 and associated inflammatory disorders. Preclinical and clinical studies are warranted in this regard.